PENERAPAN QUANTITATIVE STRATEGIC PLANNING MATRIX (QPSM) UNTUK MERUMUSKAN STRATEGI BISNIS - Indriarti, Resti; Rachmawati Chaidir, Nova (Program Studi Pendidikan Manajemen Perkantoran, 2021)
An organization or company needs strategy formulation techniques to develop strategies and objectives. Strategy formulation techniques can be grouped into three decision-making stages, namely: the input stage, the initial stage, and the decision-making stage. The tools presented in this framework are applicable to all sizes and types of organizations in defining, discovering, and selecting strategies. Descriptive method used to identify external and internal factors that affect business strategy at Malika Bakery. Based on the analysis of the Quantitative Strategic Planning Matrix (QSPM), strategic decisions that can be immediately implemented according to the attractiveness score of each alternative strategy factor, it turns out that the highest number is in the distribution channel development factor (0.60). This implies that a specific strategy to be implemented immediately is a â€œdistribution channel development strategyâ€.Keywords: Business Strategy, Strategy Formulation, QSPM